2014
DOI: 10.1186/1559-0275-11-40
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human placental syncytiotrophoblast microvesicles in preeclampsia

Abstract: BackgroundPlacental syncytiotrophoblast microvesicles (STBM) are shed into the maternal circulation during normal pregnancy. STBM circulate in significantly increased amounts in preeclampsia (PE) and are considered to be among contributors to the exaggerated proinflammatory, procoagulant state of PE. However, protein composition of STBM in normal pregnancy and PE remains unknown. We therefore sought to determine the protein components of STBM and whether STBM protein expressions differ in preeclamptic and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 45 publications
2
72
0
6
Order By: Relevance
“…45 Proteomic and lipidomic contents of microvesicles generated by syncytiotrophoblasts have also been investigated in normal and complicated pregnancies. 28,59 Microvesicles in these reports ranged from 30 nm-1 mm in size. Of the w200 lipids reported, higher levels of phosphatidylserine and lower phosphatidic acid, phosphatidylglycerol, and ganglioside mannoside 3 were reported in pregnancies complicated with preeclampsia and recurrent miscarriage compared to controls.…”
Section: Ajogorgmentioning
confidence: 97%
See 2 more Smart Citations
“…45 Proteomic and lipidomic contents of microvesicles generated by syncytiotrophoblasts have also been investigated in normal and complicated pregnancies. 28,59 Microvesicles in these reports ranged from 30 nm-1 mm in size. Of the w200 lipids reported, higher levels of phosphatidylserine and lower phosphatidic acid, phosphatidylglycerol, and ganglioside mannoside 3 were reported in pregnancies complicated with preeclampsia and recurrent miscarriage compared to controls.…”
Section: Ajogorgmentioning
confidence: 97%
“…59 Proteomic studies identified w400 proteins in the syncytiotrophoblast samples with 25 of these proteins (eg, integrins, annexins, and histones) unique to preeclampsia compared to healthy pregnant controls. 28 Exosomes as potential biomarkers of placental function Previous studies have established that extracellular vesicles, including exosomes, are released under normal physiological and pathophysiological conditions, and it has also been observed that exosome release is negligible in nonpregnant women's circulation compared to healthy normal pregnant women. 23 During gestation the rates of release of these vesicles is increased and this occurs also in response to different pathological conditions 60 presumably due to exosomal secretion from placental trophoblastic cells to the maternal peripheral circulation.…”
Section: Ajogorgmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The pathophysiological effect of circulating STBMs is associated with several nonspecific molecules that have proinflammatory and disrupting effects on the maternal endothelium only after being released from the cell (so-called danger molecules, ie, tissue factor, fibronectin, or heat shock protein). 11,20 The shedding of STBMs may be increased in response to hypoxia and reoxygenation stress that is associated with shallow placentation and leads to a cascade of maternal immunological responses that contribute to endothelial damage and maternal hypertension. 21 Necrosis likely coexists with apoptotic processes but occurs more frequently when coupled with a stressful environment.…”
Section: Extravillous Trophoblastsmentioning
confidence: 99%
“…EVs have been associated with most (patho)physiological processes studied so far (Vlassov et al, 2012;Record, 2014). EVs carry different molecular messengers: proteins, RNA (mRNA and microRNA), lipids, and small molecules (Valadi et al, 2007;Baig et al, 2014).…”
Section: Introductionmentioning
confidence: 99%